Application of the Demonstration Method in Improving Learning Outcomes on Prostration of Gratitude, Prostration of Sahwi and Prostration of Tilawah at MTS Al-Hidayah - Nuriyah, Wildah; Warsih; Sodikin, Wawan; Ruswanti, Wiwin; Warkoni (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve the learning outcomes of grade VIII students of MTs. Al-Hidayah in the material of prostration of gratitude, prostration of forgetfulness, and prostration of tilawah through the application of the demonstration method. The demonstration method was chosen because it allows students to see directly the correct practice of worship, so that they can more easily understand and remember the movements and procedures for its implementation. This study uses a classroom action approach (CAR) which is carried out in two cycles. Each cycle consists of the planning, implementation, observation, and reflection stages. Data were collected through learning outcome tests, observations, and interviews. The results of the study showed a significant increase in students' understanding and skills after the application of the demonstration method. In the first cycle, the level of student learning completeness was still relatively low, but increased in the second cycle after improvements were made to the teaching method. With the demonstration method, students are more enthusiastic and active in the learning process. They not only understand the theory, but are also able to practice prostration of gratitude, prostration of forgetfulness, and prostration of rememberfulness correctly. Therefore, this method can be an effective alternative in improving student learning outcomes in fiqh learning.